Analysis of the Effect of Car Free Day on Micro Businesses in the Kraksaan Square Area, Probolinggo - Moh Abd Rahman; Nina Ari Wahyuni; Fio Aditya Martin; Tika Yusfi Afkarina; Fahmi Nasikh Attahmidi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aims to determine the effect of Car Free Day activities on micro-enterprises in the Kraksaan square, Probolinggo. Design/methodology/approach: This study uses descriptive qualitative research where the results of the research do not contain elements of calculation and the results of the research are in the form of narratives, documentation, and interviews Findings: The Car Free Day activity has an effect on improving the economy of micro-enterprises in the Kraksaan Probolinggo square area. Research limitations/implications: The limitation of this research is that it only uses qualitative data from direct interviews in the field which depend on the perspective of each individual (micro business). Practical implications: Increased community productivity to develop their micro-enterprises and increase the level of exercise that is high. Originality/value: Our discussion departs from direct interviews with business actors, Satpol PP, event organizers at the Alun-alun and literature studies in several journals. Paper type: Research paper